A STORM* environment for building multimedia presentations - Freire, J.; Lozano, R.; Martin, H.; Mocellin, F. (Institute of Electrical and Electronics Engineers (IEEE), Computer Soc, 1998)
This paper describes an environment for constructing multimedia applications which are used to present different multimedia database objects in accordance with spatiotemporal constraints and from different sources. The main contribution of this paper is to propose an environment which integrates both a modelling case tool and an object-oriented database system.